Beyond the Pandemic: The Interplay and Biological Effects of COVID-19 on Cancer Patients -A Mini Review - Maad M. Mijwil; Abdel-Hameed Al-Mistarehi; Anas M. Zein Alaabdin; Mabel E. Ike; George Benneh Mensah; Alfred Addy (Al-SalamJournal for Medical Science, 2023)
This article delves into the relationship between COVID-19 and cancer. The challenges and effects of the COVID-19 pandemic on cancer patients are highlighted, along with an explanation of the most crucial strategies that must be adhered to avoid this virus. Explaining the importance of healthcare systems in providing services to patients and assisting them to improve their health condition. This article concentrates on recent studies and clinical observations as it allows for an accurate and comprehensive understanding of the effects of this pandemic on cancer patients. The main issues will be focused on the impact of viral infections on cancerous tumours while clarifying the long-term consequences on patients’ lives. The main goal of this article is to inform healthcare workers, physicians, and researchers about the impact and seriousness of COVID-19 on cancer patients.